KESALAHAN DALAM MENYELESAIKAN SOAL CERITA STATISTIKA SISWA KELAS IX SMP NEGERI 10 MATARAM TAHUN PELAJARAN 2024/2025 - Mardjun, Arhudawan; Harry Soeprianto; Eka Kurniawan; Sripatmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the errors made by students in solving statistical word problems based on Newman's stages. The research method used is descriptive qualitative, with the research sample consisting of Grade IX D students from SMPN 10 Mataram in the 2024/2025 academic year. Data collection was conducted through essay tests and interviews. The results showed that out of 32 students, 10 students (31%) were categorized as having a high level of errors, 15 students (47%) as having a moderate level of errors, and 7 students (22%) as having a low level of errors. The highest error occurred in the transformation stage (61%), followed by process skills (52%), encoding (50%), reading (43%), and comprehension (32%). This study highlights the importance of teaching approaches that can reduce student errors at these critical stages.